The given equation is \( x^2 + 4x + 3 = 0 \).
To complete the statements, we identify the values of \( a \), \( b \), and \( c \) in the standard quadratic form, which is \( ax^2 + bx + c = 0 \).
- The value of \( a \) is 1.
- The value of \( b \) is 4.
- The value of \( c \) is 3.
To find a solution to the equation, we can factor it:
\[ x^2 + 4x + 3 = (x + 1)(x + 3) = 0 \]
Setting each factor to zero gives us the solutions:
- \( x + 1 = 0 \) results in \( x = -1 \)
- \( x + 3 = 0 \) results in \( x = -3 \)
Therefore, one solution to the equation is -1 (but the other solution is also valid as -3). For the purpose of this answer, we will state:
One solution to the equation is -1.